Aplikasi venir buluh dan potensi dalam penghasilan perabot melalui proses acuan - Abdul Ghafur, Abdul Hamid. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Bamboo is a plant that possesses unique yet valuable bonding with life and human culture, especially among Malaysian communities. Bamboo resources in Borneo could be located in the proximity ofun explored forest such as in Tambunan, Keningau and Ranau at about 3200 hectares. The veneer's physical properties ofa bamboo are waterproof, thin and easily bent. The veneer traditional extraction and production process that was pioneered by the Bidayuh community is known as 'Berapak' and it is applied to create and produce craft products measured 12 inches wide and 30 inches long. According to literature, veneer can be used as a laminated bamboo layer and moldedfurnitur, Thefocus ofthis research was to study the characteristics ofveneer's physical properties via BS 373:1957 method such as Compression parallel to grain, Static bending and Shear. This method is used to form materials through the process ofattaching veneer with paper sheet to obtain the appropriate size that can be inserted into a molding machine. The result confirmed that the bamboo veneer sheet can be joined together and shaped peifectly to serve as potential value-added molded furniture. Hence, veneer which was derivedfrom bamboo was applied to a car seat design using contemporary and elegance elements. From the validation process, the car seat design that is incorporated with veneer has successfully satisfied the targeted consumers